2021
DOI: 10.1016/j.heliyon.2021.e08537
|View full text |Cite
|
Sign up to set email alerts
|

Factors for changes in self-care and mobility capabilities in young children with cerebral palsy involved in regular outpatient rehabilitation care

Abstract: Capabilities of children with CP improve modestly over time in outpatient rehabilitation. Children with more severe CP reach maximum mobility and self-care levels at an earlier age. After this maintaining capabilities is more realistic than improvement. Important prognostic factors are GMFCS level and intellectual impairment. Routine monitoring can aid goal setting and expectation management in communication with families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…GMFCS was one of the outcome measures taken to evaluate the difference between pre-treatment and post-treatment. According to the study done by Leeuw et al on the factors that influence change in self-care and mobility in CP children, it was concluded that GMFCS level as well as intellectual impairment for self-care, is one of the important and appropriate predictors for mobility capabilities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…GMFCS was one of the outcome measures taken to evaluate the difference between pre-treatment and post-treatment. According to the study done by Leeuw et al on the factors that influence change in self-care and mobility in CP children, it was concluded that GMFCS level as well as intellectual impairment for self-care, is one of the important and appropriate predictors for mobility capabilities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zināms, ka zemākas pašaprūpes spējas ir saistītas ar lielākiem motoro funkciju ierobežojumiem(Leeuw et al, 2021), kas kombinācijā ar šī pētījuma rezultātiem norāda uz to, ka tie jaunieši, kam ir lielāki veselības riski nākotnē (zemāks fiziskās un kognitīvās funkcionēšanas līmenis), mazāk pārzina savu veselības stāvokli, līdz ar to būtu īpaši jāsagatavo pārejai uz pieaugušo veselības aprūpi.Tematiskais bloks "Komunikācija ar medicīnas pakalpojuma sniedzējiem" kā vienīgo mērena stipruma korelāciju veidoja ar WHODAS 2.0 domēnu "Mijiedarbība ar cilvēkiem". WHODAS 2.0 domēns "Mijiedarbība ar cilvēkiem" ietver tādus aspektus kā saskarsme ar nepazīstamiem cilvēkiem, draudzības uzturēšana un saprašanās ar sev tuviem cilvēkiem, liecinot par to, ka komunikācijas uzlabošanā ar medicīnas pakalpojumu sniedzējiem, iespējams, jau pirms pārejas procesa sākšanās nozīmīga loma ir sociālās mijiedarbības veicināšanai starp jauniešiem un līdzcilvēkiemgan tuviniekiem, gan svešiniekiem.…”
unclassified